The need for a food allergy educator program for allied healthcare professionals in Canada - Jennifer L. P. Protudjer; Carina Venter; Marion Groetch; Tara Lynn Mary Frykas; Jasmin Lidington; Harold Kim (Allergy, Asthma & Clinical Immunology, 2022)
Abstract Owing to a collaborative approach to patient care, and a paucity of allergists in Canada, there is a need to develop a food allergy educational program for allied health care professionals in Canada. Such programs already exist in the United States and Britain. Herein, we describe the outcomes of recent conference proceedings to inform the educational needs for such a program. As part of the 76th Annual Meeting of the Canadian Society of Allergy and Clinical Immunology (CSACI), held virtually due to the COVID-19 pandemic, we hosted a virtual workshop on the need for a food allergy educator program for Canadian allied health professionals. This workshop was co-developed with the CSACI and an industry partner, and featured allergy specialist dietitians. Attendance was open to all conference delegates, and to allied health professionals. As part of the registration process, registrants posed diverse food allergy-related questions, ranging from how to use an epinephrine autoinjector, to daily management and, how to cure food allergy. A national food allergy educator program will empower both allergy and non-allergy specialist healthcare professionals to appropriately counsel patients. This virtually-delivered program will begin to close a gap in healthcare access resulting from the geographic size of Canada, as it will enhance allied healthcare providers’ confidence to provide evidence-based food allergy care appropriately for those with food allergy.